2010
DOI: 10.1177/1477370810378116
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for aggression in pre-adolescence: Risk domains, cumulative risk and gender differences - Results from a prospective longitudinal study in a multi-ethnic urban sample

Abstract: This article reviews a range of risk factors for aggression at age 11 derived from a prospective longitudinal study on the social development of children in a large multi-ethnic sample in Switzerland. The study uses a multi-informant approach that permits reliance on combined measures of social behaviour and covers factors derived from a wide range of risk domains. Besides analysing the effects of individual risk factors, the study also investigates the effect size of cumulative risk within and across risk dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 80 publications
1
63
0
Order By: Relevance
“…The observed higher rate of violence perpetration of boys (cf. [18,27]), the observed higher preference of boys for violent media content (cf. [5,28]) as well as the observed lower empathic scores of boys (cf.…”
Section: Summary Of Findings and Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed higher rate of violence perpetration of boys (cf. [18,27]), the observed higher preference of boys for violent media content (cf. [5,28]) as well as the observed lower empathic scores of boys (cf.…”
Section: Summary Of Findings and Theoretical Implicationsmentioning
confidence: 99%
“…[23,24]), and between higher violent content consumption and a higher rate of aggressive behavior (cf. [17,18]). Effect sizes were shown to lie within the range of meta-analytic results reported in the introduction [7][8][9].…”
Section: Summary Of Findings and Theoretical Implicationsmentioning
confidence: 99%
“…A risk factor for offending is a variable that predicts a high probability of later offending (Farrington, Loeber & Ttofi, 2012;Ribeaud & Eisner, 2010). Some authors (Haines & Case, 2008) point out that risk factors can vary greatly.…”
mentioning
confidence: 99%
“…Once this association has been corroborated, the main focus is on a sequential test of hypotheses regarding the nature of the relationship. First, we explore if the relationship is spurious, i.e., whether it can be "explained away" by unobserved and by observed time-varying and time-invariant covariates that previous research has identified as key predictors of aggression and delinquency in a large range of risk domains (see e.g., Farrington, 1998;Hawkins et al, 1998;Ribeaud & Eisner, 2010b;Wikström & Butterworth, 2006). Specifically, we consider self-control as a key personality characteristic related to aggression and delinquency (Gottfredson & Hirschi, 1990) as well as parenting behavior, substance use, adult media use, deviant peers, unstructured leisure activities, peer victimization, parental SES, migration background, gender, and age.…”
Section: Aim Of the Present Studymentioning
confidence: 99%
“…The analyses are based on data from the Zurich Project on the Social Development of Children and Youths, an experimental prospective longitudinal study on the development of aggressive and other antisocial behavior that was set-up in an culturally diverse urban context in Europe (e.g., Eisner, Malti, & Ribeaud, 2012;Ribeaud & Eisner, 2010b). The initial target sample consisted of 1675 children who entered one of 56 randomly selected public schools in the city of Zurich, Switzerland, at age 7 in 2004.…”
Section: Sample and Participantsmentioning
confidence: 99%